Pembinaan Kelompok Swadaya Masyarakat Melalui Penguatan Manajemen Keuangan Sesuai Dengan Standar Akuntansi Keuangan Entitas Privat (SAK EP) - Wardhana, Rony; Anam, Saiful; Wijaya, Agung; Malindo, Tito (Asthadarma : Jurnal Pengabdian Kepada Masyarakat, 2025)
The objective of this program is to enhance the financial management of Badan Keswadanaan Masyarakat (BKM) in Mojokerto district, with the aim of ensuring compliance with the Financial Accounting Standards for Private Entities (SAK EP). BKM, in its capacity as a community entity that oversees financial resources and initiatives aimed at fostering empowerment, is obligated to meticulously prepare financial reports that adhere to the principles of transparency, accountability, and standardization. Nevertheless, various obstacles persist, including a deficiency in accounting comprehension, inadequate documentation, and insufficient internal control systems. The activity employs a multifaceted approach encompassing mentoring, training, and technical consultation. The objective of this approach is to facilitate the preparation of financial reports in accordance with SAK EP, enhance audit readiness, and optimize the internal control system. The findings of the activity demonstrated an enhancement in the preparation of the income statement, statement of changes in equity, and notes to the financial statements (CALK). Concurrently, the BKM management initiated the implementation of comprehensive documentation and audit procedures for cash, receivables, and fixed assets. The program is expected to serve as a sustainable foundation for strengthening the financial capacity of BKM and encouraging the creation of professional financial management practices at the community level.